The Making and Unmaking of Urban Citizenship in the Maspero Triangle - Abd El Razek, Nadine (AUC Knowledge Fountain, 2023)
Cairo is undergoing a moment of sharpened exclusion and inclusion, with the city’s residents of informal settlements disproportionately experiencing displacement and abrupt interruptions to their social fabric to make way for investment opportunities. In pursuit of achieving the status of a global city, the Egyptian state has effectively widened its practice of structural violence, in order to accumulate capital through dispossession. In the process of doing so, the state has problematized the contested status of urban citizenship, disenfranchising the urban dwellers of Cairo from their right to the city. Following the temporal shifts in the negotiation for urban citizenship, the story of displacement in the Maspero triangle is invoked in order to analyze the policies and practices that delineate the scope and essence of political rights for the urban citizens of Cairo. This research aims to contribute to an understanding of the subjectivities that are produced through a perpetually shifting spatiotemporal order.